Integrative Genomic Analysis Predicts Regulatory Role of N6-Methyladenosine-Associated SNPs for Adiposity - Lin, Weimin; Xu, Hao; Yuan, Quan; Zhang, Shiwen (Frontiers in Cell and Developmental Biology, 2020)
Genome-wide association studies have identified many susceptible loci to explore the genetic factors of adiposity. However, the specific mechanisms by which these SNPs (single nucleotide polymorphism), particularly in the non-coding region, are involved in the pathogenesis of adiposity remain unclear. Recently, genetic variation is thought to affect N6-methyladenosine (m6A) RNA modification, which is the most common post-transcriptional messenger RNA modification. In this study, we identified a large number of BMI (body mass index)-associated m6A-SNPs from published GWAS summary statistics through a public database and explored their potential mechanisms involved in the pathogenesis of adiposity. In summary, the intergrative analysis detected 20993 BMI-associated m6A-SNPs and 230 m6A-SNPs which reached the genome-wide suggestive threshold (5.0E-05), while 215 of them showed eQTL signals and 167 are the corresponding genes. The leading SNP rs8024 (C/A) was located next to the m6A modification site of 3’UTR of the IPO9 gene, which was predicted to affect the m6A modification site and regulate the expression of the IPO9 gene to participate in the pathogenesis of adiposity. This m6A-SNP/gene expression/adiposity triplets provide a new annotation for the pathogenic mechanism of adiposity risk loci identified by GWAS.